2014
DOI: 10.20533/ijcdse.2042.6364.2014.0268
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Climate Change: Reasons, Consequences, and Willingness to Act. How Aware are They?

Abstract: This paper reports a study conducted to investigate social studies and science teachers' awareness on climate change and how professional development workshop "Awareness and Adaptation to Climate Change" affects teachers' awareness level. For this purpose, a total of 101 teachers from 8 different cities and 4 geographical locations participated in the workshops and took part in the study. For data collection purposes, the Awareness to Climate Change Questionnaire (ACCQ) was used. Analysis revealed no statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…When pre-service teachers' awareness of industrial developments aimed at mitigating the effects of climate change is examined, it is discovered that they developed an awareness of the use of sanctions and penalties, waste control, and the use of locally sourced raw materials. Previous research on industrial initiatives' awareness has identified energy savings, the use of environmentally friendly materials, and system improvement (Dal et al, 2014;Halady & Rao, 2010). This study's pre-service teachers were also aware of the importance of using environmentally friendly materials and conserving energy.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…When pre-service teachers' awareness of industrial developments aimed at mitigating the effects of climate change is examined, it is discovered that they developed an awareness of the use of sanctions and penalties, waste control, and the use of locally sourced raw materials. Previous research on industrial initiatives' awareness has identified energy savings, the use of environmentally friendly materials, and system improvement (Dal et al, 2014;Halady & Rao, 2010). This study's pre-service teachers were also aware of the importance of using environmentally friendly materials and conserving energy.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…En su estudio global (Lee et al, 2015) confirman que educación fue un factor común entre los países, especialmente en Estados Unidos y China, para predecir conciencia sobre cambio climático. Varios estudios en diferentes países confirman este resultado, a través de una auto percepción de docentes con conocimiento deficiente, limitada disponibilidad de herramientas de enseñanza y poca o ninguna investigación (Cajigal et al, 2016;Dal, et al, 2014;Domenech-Casal, 2014; García-Rodeja y Lima, 2012; Meira-Cartea y Arto-Blanco, 2014; Saidón y Claverie, 2016).…”
Section: Discussionunclassified
“…Varios estudios confirman una auto percepción de docentes con deficiencias en conocimiento ambiental; limitada disponibilidad de herramientas de enseñanza en el tema y poca investigación (Domenech-Casal, 2014;García-Rodeja y Lima, 2012; Saidón y Claverie, 2016). También poco o confuso conocimiento de maestros y alumnos sobre el cambio climático y la gestión de riesgo de desastres (Cajigal et al, 2016;Dal, et al, 2014; Meira-Cartea y Arto-Blanco, 2014; Saidón y Claverie, 2016). Esa percepción mundial, tambien se percibió para el cuerpo docente universitario en Honduras, previo a este estudio, en parte porque no se identificaron mayores iniciativas de formación en el tema de cambio climático y de GIRD.…”
Section: Introductionunclassified
“…Review of the literature reveals that knowledge about CC has been approached from varying perspectives, mainly including general knowledge of CC (e.g., Barimah et al, 2012;David, 2015;Orlove et al, 2010;Sundblad, Biel, & Gä rling, 2009); knowledge of causes and/or effects of CC (e.g., Dal, Ozturk, & Alper, 2014;Oruonye, 2011;Yang et al, 2018); and knowledge of health impacts of CC (e.g., Kabir et al, 2016;Nigatu, Asamoah, & Kloos, 2014;Sulistyawati, Mulasari, & Sukesi, 2018). Many other issues related to CC have been studied as well, including awareness and/or perception of CC (e.g., Barreda, 2018;Jamshidi et al, 2018;Ochieng & Koske, 2013;Rahman et al, 2014;); awareness of CC risk (e.g., Etkin & Ho, 2009;Shukla et al, 2019;Sullivan & White, 2009;Xie et al, The foregoing three literature review paragraphs highlight lack of Arab studies of knowledge about CC, neither amongst university students, nor among any other population, whether in Jordan or in any other Arab country.…”
Section: Climate Change Knowledge Research: Briefingmentioning
confidence: 99%